Social Movements in Southeast Sulawesi, 1906-1942 - La Ode Rabani (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2010)
The social movement in period of 1906-1942 started with the intervention of the Dutch colonial government to the economic income resources of the people which then triggered social chaos and unrest marked by open conflict and opposition between the Dutch and the indigenous people of South East Celebes. The collection of personal tax, the reduction of economic resources of traditional authorities such as port tax and levy, tobacco tax, export import tax, and others created instability and unrest at the level of traditional authorities as well as low class people who had been always the objects of tax. The opposition of the local people indicated the existence of strong refusal to the economic condition which was going on among the indigenous people, even when it was done by the local authorities or sultanate of Buton. So, it can be understood that the social movement was caused not only by political factors, but also by economic factors intervened by the intervention of external power.